Pengaruh Komunikasi Interpersonal terhadap Kinerja Aparat di Desa Tinelo Ayula Kecamatan Bulango Selatan - Arief Abdul Gani; Meyko Panigoro; Melizubaida Mahmud; Radia Hafid; Roy Hasiru (Departement of Mathematics Education, 2022)
The research objectives that have been stated previously are that the researcher wants to measure the magnitude of the influence of interpersonal communication on the performance of apparatus. Tinelo Ayula Village, Bulango Selatan District, the effect is obtained between the interpersonal communication variable and the village apparatus performance variable. In this study, researchers used quantitative data analysis methods by distributing questionnaires to respondents as a sample in this study with a total sample of 40 people. Data collection techniques used in this study were Observation, Interview Interviews, Questionnaires/Questionnaires and Documentation as well as Data Analysis Techniques in this study using Descriptive Analysis Analysis Techniques, Data Normality Test, and Simple Linear Regression Analysis. The results of the analysis of the coefficient of determination in the table above show that the adjusted determination coefficient or the R Square number is 0.520. or 52.0% This value indicates that 0.52% of apparatus performance variability can be explained by the interpersonal communication variable, while the remaining 42.0% is explained by other variables not examined in this study. Based on the results of the research in the previous chapter, it can be concluded that Interpersonal Communication has a significant positive effect on the performance of Tinelo Ayula Village Officials, Bulango Selatan District. This result is evidenced by the t-count value of 2.280 which is greater than the t-table of 2.02439 and a significance value of 0.000 or less than 0.05. These results indicate that by implementing interpersonal communication with officials, it can improve the performance of Tinelo Ayula Village officials, Bulango Selatan District.